2020
DOI: 10.1002/ehf2.12900
|View full text |Cite
|
Sign up to set email alerts
|

6 min walk test is a strong independent predictor of death in outpatients with heart failure

Abstract: Aims The aim of this study was to examine the prognostic value of the 6 min walk test (6MWT) in a large cohort of outpatients with heart failure. Methods and results A total of 5519 outpatients with heart failure from the National Norwegian Heart Failure Registry (NNHFR), which is part of the Norwegian Cardiovascular Disease Registry, were included in this analysis. The NNHFR recommended the use of the 6MWT for prognostic assessment of all patients included in the registry. Patients were categorized according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…A systematic review of 14 studies found that the 6-minute walk test results correlated moderately with peak VO 2 levels and were a reliable and valid indicator of functional capacity in patients with HF who did not walk >490 m. 8 Distance walked in the 6-minute walk test has been associated with prognosis in HF across multiple studies. 9–13,15,16,27 A cutoff of <300 m roughly correlates to patients with NYHA class III to IV symptoms and is associated with worse 3-year survival free of heart transplant (62% versus 82% for those walking ≥300 m). 27 Dyspnea is a complex symptom that can reflect abnormalities in a number of different systems and can be influenced by psychological and environmental factors.…”
Section: Initial and Serial Evaluationmentioning
confidence: 99%
“…A systematic review of 14 studies found that the 6-minute walk test results correlated moderately with peak VO 2 levels and were a reliable and valid indicator of functional capacity in patients with HF who did not walk >490 m. 8 Distance walked in the 6-minute walk test has been associated with prognosis in HF across multiple studies. 9–13,15,16,27 A cutoff of <300 m roughly correlates to patients with NYHA class III to IV symptoms and is associated with worse 3-year survival free of heart transplant (62% versus 82% for those walking ≥300 m). 27 Dyspnea is a complex symptom that can reflect abnormalities in a number of different systems and can be influenced by psychological and environmental factors.…”
Section: Initial and Serial Evaluationmentioning
confidence: 99%
“…Мнение о прогностической значимости ТШХ поддерживается в других работах при менее продолжительном периоде наблюдения, но у больных с установленной ХСН с нормальной и сниженной ФВ. Так, в крупнейшем исследовании, включавшем 5519 больных, показано, что ТШХ является сильным независимым предиктором смерти в амбулаторных условиях при ХСН в течение двух лет наблюдения [14].…”
Section: Discussionunclassified
“…To examine changes in submaximal exercise capacity at patient level, differences between the 6MWT at baseline and after 3 months were calculated per patient. 10 …”
Section: Methodsmentioning
confidence: 99%
“…The distance walked on the 6MWT is correlated with exercise duration and oxygen uptake at peak exercise and is used to assess interventions or determine subgroups of patients that might benefit from certain interventions 7–9 . The 6MWT has been shown to have a strong predictive power for both mortality and morbidity in patients with HF 10–12 . In a study of 1714 patients with HF, a decline in 6MWT was found to be associated with a worse prognosis and not modified by treatment up‐titration 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation